PENGARUH BAHAN BAKU, TENAGA KERJA, DAN DISTRIBUSI TERHADAP PENDAPATAN UMKM DI KABUPATEN SUMENEP (Studi Kasus UMKM Kerupuk Amplang Bintang - Nabilatur Rahmah, Silmi; Hadyarti, Vidi (Universitas Islam Lamongan, 2024)
This research aims to determine the influence of raw material, labor and distribution variables on the income of Amplang Bintang Crackers MSMEs located in Sumenep Regency. This research applies quantitative methods and uses secondary data with multiple regression analysis. Data was collected through financial records of the Amplang Bintang Sumenep Crackers business for the 2021-2023 period, supported by interview techniques. The sample from the study consisted of 36 people obtained from monthly data for 3 years. The research findings show that there is a significant influence of raw materials on income, while labor also has a significant influence on income, distribution also has a significant influence on income, and simultaneously the variables raw materials, labor and distribution have a positive influence and significant impact on the income of Amplang Bintang Crackers Sumenep MSMEs.